Costs of treatment change following first-line somatostatin analog monotherapy among patients with neuroendocrine tumors. (1st January 2021) - Tawfik, Bernard; Ray, David; Moynihan, Meghan; Princic, Nicole
Abstract: Background: This study describes treatment characteristics and healthcare costs prior to and following treatment change from somatostatin analog (SSA) monotherapy among a privately-insured NET patient population in the US. Methods: Patients with newly diagnosed NET and treated with SSA monotherapy were retrospectively identified in IBM MarketScan claims between 1/1/2014 and 3/31/2019. NET treatment change was captured ≥30 days after the SSA start date (earliest new treatment = index date). Healthcare costs (reimbursed amount in 2019 dollars) were reported for 1, 3, and 6 months pre- and post-index intervals. Results: A total of 305 patients were identified (mean age: 58 years; female: 52%; metastatic disease: 49%). Most patients started on octreotide (81%) vs. lanreotide (19%). Common treatment changes included alternate SSA (38%), targeted therapy (30%), or chemotherapy (23%). Total costs increased on average by $13, 272 between the month preceding and following treatment change ( p  < .001), with the highest increase among patients changing to targeted therapy ($19, 677, p  < .001) vs. an alternate SSA ($10, 240, p  < .001) or chemotherapy ($4, 057, p  = .155). The trajectory in mean cost difference using a 1, 3, and 6-month time period followed an increasing trend for patients who changed to targeted therapy (Δ$19, 677, Δ$34, 856, Δ$58, 387) but was flat for patients who changed to the alternate SSA (Δ$10, 240, Δ$10, 026, Δ$11, 727). Conclusions: Higher total healthcare costs were observed following treatment change from first-line SSA. Switching to the alternate SSA was associated with a fixed, one-time cost; whereas, switching to targeted therapy was associated with both an initial switching cost and a persistent monthly increase.